2011
DOI: 10.1161/circulationaha.110.973222
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy With Tolerogenic Apolipoprotein B-100–Loaded Dendritic Cells Attenuates Atherosclerosis in Hypercholesterolemic Mice

Abstract: Tolerogenic DCs pulsed with ApoB100 reduced the autoimmune response against low-density lipoprotein and may represent a novel possibility for treatment or prevention of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
145
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 45 publications
0
145
0
2
Order By: Relevance
“…Dendritic cells can also be used to confer tolerance to self-antigens. Intravenous administration of dendritic cells pulsed with the complete apoB protein and IL-10 reduces atherosclerosis by a mechanism involving activation of regulatory T cells (56). Taken together, these data imply that immunizations with self-antigens boosts existing regulatory T cell immunity and that breaking the tolerance to self-antigens may be an important contributor to atherosclerosis development (49,57).…”
Section: Emerging Therapies Promoting Regulatory T Cell Responsesmentioning
confidence: 83%
“…Dendritic cells can also be used to confer tolerance to self-antigens. Intravenous administration of dendritic cells pulsed with the complete apoB protein and IL-10 reduces atherosclerosis by a mechanism involving activation of regulatory T cells (56). Taken together, these data imply that immunizations with self-antigens boosts existing regulatory T cell immunity and that breaking the tolerance to self-antigens may be an important contributor to atherosclerosis development (49,57).…”
Section: Emerging Therapies Promoting Regulatory T Cell Responsesmentioning
confidence: 83%
“…14 A cell-based therapy strategy using tolerogenic DCs revealed that apolipoprotein B100 (apoB100)-pulsed tolerogenic DCs inhibit the proliferative and proinflammatory T-cell response to apoB100, promoted Treg induction, and reduced atherosclerotic lesion formation. 22 Oral administration of Hsp60 or Hsp65 might also induce Tregs in the gastrointestinal tract and affect atherogenesis (Figure 3). 23 Although further studies are needed to clarify the precise role of the several types of vascular DCs in atherogenesis, effective methods to induce atheroprotective DCs could be novel therapies for prevention of atherosclerosis.…”
Section: Proinflammatory and Antiinflammatory Immune Responses In Athmentioning
confidence: 99%
“…Treatment of disease-prone hypercholesterolemic mice with a single injection of tolerogenic DC led to significantly reduced atherosclerosis [14].…”
Section: Vaccination Strategies Based On Epitopes Of Oxidized Ldlmentioning
confidence: 95%
“…Additional immunotherapeutic approaches have been recently evaluated with promising results [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%